Motivasi Santri dalam Menghafal Al-Qur’an di Pondok Pesantren Berbasis Kitab Kuning - Prabowo Prabowo (STIKes Ibnu Sina Ajibarang, 2024)
Memorizing the Qur'an is an activity that is not easy to do. It takes a long time, extra energy and thought and high motivation. Especially if someone memorizes the Qur'an in a yellow book-based boarding school will have many activities to follow and many obstacles to face. Therefore, everyone who memorizes the Qur'an has intrinsic and extrinsic motivation. This motivation helps students to finish their memorization quickly with good memorization quality without leaving other activities. This study aims to determine the motivation of students in memorizing the Qur'an in yellow book-based Islamic boarding schools. This type of research is qualitative research with a case study approach. This research was conducted at the Haji Ya'qub Islamic Boarding School which is one of the units of the Lirboyo Islamic Boarding School. Data collection techniques were conducted through interviews, observation, and documentation. By using data analysis using data reduction, data presentation, and conclusion drawing. The results of this study include: 1) Motivation that arises from the students themselves (intrinsic motivation) owned by students in memorizing the Qur'an, namely: a. Desire to become a memorizer of the Qur'an, b. Get closer to Allah, c. Complete knowledge, and d. Make parents happy. Make both parents happy. 2) Motivation that will function due to external stimuli (Extrinsic motivation) owned by students in memorizing the Qur'an, namely: a. Encouragement from the family, especially both parents and 2) encouragement from the ustadz or mualim tahfidz.